Radiotherapy-Induced Digestive Injury: Diagnosis, Treatment and Mechanisms - Chen, Guangxia; Han, Yi; Zhang, Haihan; Tu, Wenling; Zhang, Shuyu (Frontiers in Oncology, 2021)
Radiotherapy is one of the main therapeutic methods for treating cancer. The digestive system consists of the gastrointestinal tract and the accessory organs of digestion (the tongue, salivary glands, pancreas, liver and gallbladder). The digestive system is easily impaired during radiotherapy, especially in thoracic and abdominal radiotherapy. In this review, we introduce the physical classification, basic pathogenesis, clinical characteristics, predictive/diagnostic factors, and possible treatment targets of radiotherapy - induced digestive injury. Radiotherapy-induced digestive injury complies with the dose-volume effect and has a radiation-based organ correlation. Computed tomography (CT), MRI (magnetic resonance imaging), ultrasound (US) and endoscopy can help diagnose and evaluate the radiation-induced lesion level. The latest treatment approaches include improvement in radiotherapy (such as shielding, hydrogel spacers and dose distribution), stem cell transplantation and drug administration. Gut microbiota modulation may become a novel approach to relieving radiogenic gastrointestinal syndrome. Finally, we summarized the possible mechanisms involved in treatment, but they remain varied. Radionuclide-labeled targeting molecules (RLTMs) are promising for more precise radiotherapy. These advances contribute to our understanding of the assessment and treatment of radiation-induced digestive injury. Key words: ionizing radiation, radiation-induced digestive injury, gut microbiota, gland transfer